2017
DOI: 10.1089/sur.2016.183
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors Associated with Surgical Infections among Spine Patients

Abstract: Interventions focusing on minimizing patient-specific risk factors and operation-specific risk factors and optimizing patient-specific protective factors and operation-specific protective factors are most effective in minimizing the likelihood of a post-operative infection among patients undergoing orthopedic spinal surgical procedures. The studies reviewed provide conflicting evidence relative to risk and protective factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
1
34
0
2
Order By: Relevance
“…37 It should be noted that antibiotic dosage (cefazolin <20 mg/kg) needs to be adjusted appropriately in obese patients to be effective in reducing infection risk. 38,39 It should also be noted that antibiotics should be redosed every 4 hours or after 1500 mL of blood loss in spinal deformity cases. 40 Furthermore, special consideration must be made to recognize patients that are at risk for harboring gram-negative species, such as incontinent patients or those that have a history of urinary tract colonization.…”
Section: Preoperative Antibioticsmentioning
confidence: 99%
“…37 It should be noted that antibiotic dosage (cefazolin <20 mg/kg) needs to be adjusted appropriately in obese patients to be effective in reducing infection risk. 38,39 It should also be noted that antibiotics should be redosed every 4 hours or after 1500 mL of blood loss in spinal deformity cases. 40 Furthermore, special consideration must be made to recognize patients that are at risk for harboring gram-negative species, such as incontinent patients or those that have a history of urinary tract colonization.…”
Section: Preoperative Antibioticsmentioning
confidence: 99%
“…20 Increased tissue necrosis from retraction injury may also contribute. 4,5 However, some studies have failed to find a relationship between obesity and SSI. 21,22 These variable findings may be related to comorbid conditions that manifest with obesity, such as diabetes, as well as differences in surgical technique.…”
Section: Patient Factorsmentioning
confidence: 99%
“…40 In addition, the antibiotic dosage (cefazolin <20 mg/kg), should be adjusted with regard to obese patients in order to further reduce the risk of infection. 4,18 It is also important to note the need to redose the antibiotics every 4 hours and, in spinal deformities, after 1500 mL of blood loss due to the washout effect. 41,42 Skin Cleansing.…”
Section: Patient Factorsmentioning
confidence: 99%
“…Despite our careful randomisation of the study arms, we found that the antibiotics group had a considerably higher proportion of females than the control group (80.6% vs 63.6%), although the difference did not reach statistical significance. Some previous studies of SWI at other anatomic sites reported a higher risk in female patients, whereas others showed a higher risk in male patients . In the head and neck literature, Man et al found no sex difference in the rate of SWI following neck dissection, and Shkedy et al found that women had a higher incidence of SWI after parotidectomies than men.…”
Section: Discussionmentioning
confidence: 97%